The Effect Of Training, Work Ability And Work Experience On Performance Of Contract Workers In Bandung Kebonjati Hospital - Muhammad Vebby Goena Putra (International Journal of Economics, Business and Innovation Research, 2026)
The phenomenon that occurs in contract employees at Kebonjati Hospital currently shows that there are some senior employees who have long work experience or have worked for more than 3 years but have not experienced performance improvement. In addition, with longer work experience, there are still few employees with sufficient work experience, lack of training. Most senior employees assume that training is only necessary for new employees and is not part of the company's work plan to improve performance. The purpose of this study was to determine the effect of training, work ability and work experience on the performance of contract employees in Kebonjati Hospital. This type of research this study is a quantitative research with the source data used in this study in the form of questionnaires distributed and filled by respondents who are contract employees at Kebonjati Hospital. The population of this study was 48 contract employees at Kebonjati Hospital. The test results showed that training had no significant effect on the performance of contract employees at Kebonjati Hospital Bandung evidenced by the value of t count 0.916 < 1.677 with significance 0.365 > 0.05. Work ability has a significant effect on the performance of contract employees at Kebonjati Hospital Bandung evidenced by the value of t count 3.003 > 1.677 with significance 0.004 < 0.05. Work experience has a significant effect on the performance of contract employees at Kebonjati Bandung hospital evidenced by the value of t count -2.321 > 1.677 with significance 0.025 < 0.05. In addition, training, skills and work experience simultaneously have a significant effect on the performance of contract employees at Kebonjati Bandung hospital evidenced by the calculated F value of 4,182 with significance of 0,011 < 0.05.